A novel approach to analyse adhesive layer strain field in a stepped lap repaired carbon fiber reinforced polymer panel using digital image correlation. Issue 19 (18th October 2017) - Matta, Seshadri; Chinthapenta, V.; Ramji, M.
Abstract: The present work focuses on the critical strain analysis of thin adhesive layer present in single-sided stepped lap-repaired carbon fibre-reinforced polymer panels subjected to tensile loading. Digital image correlation technique is used for acquiring both the global and local whole field strain, to obtain the longitudinal, peel, and shear strain distribution over the adhesive layer. The evolution of strain field with increasing load is captured to predict its mechanical behaviour. Magnified optics is used to capture the localized strain field at critical zones. Step corners are identified as critical zones of damage. Debonding is observed as the primary source of damage in the adhesive layer. Overall, the load displacement behaviour and damage mechanism are captured from the experiment. A numerical study based on finite-element analysis is carried out for validating the experimental results. In the numerical study, the adhesive layer is modelled using zero thickness contact element with cohesive behaviour to mimic disbonding. The cohesive zone properties for mode-I and mode-II loading are experimentally obtained from DCBt to ENF test respectively. Microscopic load vs. displacement curve obtained from an experiment is found to be in good correlation with FE estimates.